2022
DOI: 10.3390/ani12233424
|View full text |Cite
|
Sign up to set email alerts
|

Cheese and Butter as a Source of Health-Promoting Fatty Acids in the Human Diet

Abstract: The assessment of fatty acid composition, including the content of conjugated linoleic acid cis9trans11 C18:2 (CLA) and trans C18:1 and C18:2 isomers in fat extracted from selected high-fat dairy products commonly available to consumers in retail sale on the Polish market, and a comparison of their indicators as to the quality of lipids was the aim of the study. The experimental materials were hard cheeses, white-mold cheeses, blue-veined cheeses, and butters. The conducted study demonstrated that various cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…These indices consider the different effects that individual fatty acids may have on human health. The thrombogenicity index value indicates the propensity to form blood clots in blood vessels [29].…”
Section: Resultsmentioning
confidence: 99%
“…These indices consider the different effects that individual fatty acids may have on human health. The thrombogenicity index value indicates the propensity to form blood clots in blood vessels [29].…”
Section: Resultsmentioning
confidence: 99%
“…It is responsible for anti-atherosclerotic, antioxidative, and anti-inflammatory activities. Isolation of oleic acid [cis9trans11 C18:2 [49]] from hard cheeses and blue cheeses had shown to have cardio protective properties [75,76]. Cheese has a high concentration of vitamin K2; which functions in lowering vascular calcification [77].…”
Section: Cardioprotective Activitymentioning
confidence: 99%
“…Van Hoogdalem et al thought that medium-chain fatty acids contained in emulsions might be nontoxic and effective for poorly absorbed drugs, and they demonstrated that the rectal absorption of cefoxitin could be improved by the concomitant administration of caprylic acid (C8) and capric acid (C10) [ 88 ]. C8 and C10 are originally derived from food ingredients, and these additives are abundant in dairy milk products [ 89 ]. Additionally, C8 and C10 have been clinically applied for the development of many drugs in humans, as follows.…”
Section: Technology To Improve Oral Absorption Of Middle-to-large Mol...mentioning
confidence: 99%
“…Safety: Fatty acids have been regarded as safe additives [ 89 ]. Moreover, previous in vivo studies indicated that C8 and C10 are safe additives, as follows.…”
Section: Technology To Improve Oral Absorption Of Middle-to-large Mol...mentioning
confidence: 99%